Another Life : Lawrence After Arabia - Simpson, Andrew R. B. (Malta Pellmount, 2011)
With interviews of people who knew Lawrence and study of primary sources, Andrew Simpson explores the later life and mysterious death of one of the most charismatic figures of the 20th century.
Include Illustrations and Appendix
Keywords: Great Britain -- Soldiers